Stiff2f - kb(3,5)=-kb(2,6 kb(3,6)=.5*kb(3,3 kb(5,5)=kb(2,2 kb(5,6)=-kb(2,6 kb(6,6)=kb(3,3 for i=2:6 for j=1:i-1 kb(i,j)=kb(j,i end end o3=zeros(3

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Sheet1 Page 1 function [k]=stiff2f(L,ll,aa) kb=zeros(6) l=ll(1) m=ll(2) EA=aa(1)*aa(2) EI=aa(1)*aa(3) kb(1,1)=EA/L kb(1,4)=-kb(1,1) kb(4,4)=kb(1,1) kb(2,2)=EI*12/L^3 kb(2,3)=6*EI/L^2 kb(2,5)=-kb(2,2) kb(2,6)=kb(2,3) kb(3,3)=4*EI/L
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: kb(3,5)=-kb(2,6) kb(3,6)=.5*kb(3,3) kb(5,5)=kb(2,2) kb(5,6)=-kb(2,6) kb(6,6)=kb(3,3) for i=2:6 for j=1:i-1 kb(i,j)=kb(j,i) end end o3=zeros(3) t=[l,m,0-m,l,0 0,0,1] T=[t,o3 o3,t] k=T'*kb*T...
View Full Document

This note was uploaded on 06/07/2011 for the course EML 4507 taught by Professor Kim during the Fall '11 term at University of Florida.

Ask a homework question - tutors are online